Keanekaragaman Tumbuhan Obat di Sekitar Hutan Dusun Totodoku Kecamatan Wasile Timur Kabupaten Halmahera Timur - Reyna Ashari; Asiah Salatalohy (Jurnal Hutan dan Masyarakat, 2021)
Totodoku Village in East Wasilei District is inhabited by people from the Tobelo Dalam Tribe. This community was a tribal community from the forest and still uses medicinal plants from the forest. Unfortunately, knowledge about medicinal plants can change when there is excessive land exploitation or interaction with people from other tribes. Its application will change if it is not passed on to the modern younger generation. This study aims to identify the diversity of medicinal plants and their uses in Totodoku Village. This research was conducted in October - December 2020. Data were collected by surveying medicinal plants in 4 transects and interviewing the community regarding the use of medicinal plants. The data were analyzed to obtain the Important Value Index (IVI) and describe its uses. There were 29 species of medicinal plants from 21 families. The dominant species were kirinyuh (Chromolaena odorata) which is used to treat cysts, diabetes and ulcers; and awar-awar (Ficus septica) as a medicine to strenthen joints and has anti-inflammatory effects. The seedling and sapling phases were dominated by Chromolaena odorata, the IVI values were 41.60% and 55.9%, respectively. The pole phase was dominated by Ficus septica with IVI of 39.08 The species diversity index was in the medium category (H’=2.605), while the species evenness index is fairly evenly distributed (E=0.77). Utilizations of medicinal plants is done by drinking them (26 species) and sticking them on the sick body parts (3 species).